MUKTAMAR 2015 DAN POLITIK NU DALAM SEJARAH KENEGARAAN - Moh Rosyid (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2015)
NU and its followers is a national asset that needs to be affirmed by the state. Since its establishment, NU has colored the journey of the nation. This is confirmed by the number of NU figures who became national heroes, public officials and others. However, as mass organization, NU finds difficulties to contribute in politics, so they look back to the 1926 khittah. As one of Muslim organization, NU is expected to respect and care for others including their opponents. NU Muktamar in Jombang, East Java August 2015 showed the political dynamics within NU, between two groups: proponents of Ahlul halli wal aqdi (AHWA) and its opponents.